Predictive Value of Systemic Immune Inflammation Index, Aggregate Index of Systemic Inflammation, and Systemic Inflammation Response Index in Lower Extremity Deep Venous Thrombosis Following Severe Trauma - Li, Peng-Fei; Lu, Xin; Zhou, Yu-Qian; Wang, Ke; Yang, Peng; Chen, Xiong-Hui; Xu, Feng (Chinese medical sciences journal, 2024)
Venous thromboembolism is a highly prevalent condition after polytrauma, and recognized as an important factor contributing to poor prognosis. The aim of this study was to investigate the risk factors for lower extremity deep venous thrombosis (LEDVT) in a severely traumatized population and to evaluate their predictive value for LEDVT. This was a retrospective, single-center observational study. All subjects were severely traumatized patients who were admitted to the Traumatic Intensive Care Unit from January 2021 to May 2024. Based on Doppler ultrasound findings of both lower extremities from the time of injury to 30 days post-injury, patients who developed LEDVT were enrolled in the LEDVT group, and those who did not develop LEDVT were enrolled in the NLEDVT group. Demographic, clinical, and laboratory data were collected upon admission. Multivariable logistic regression analysis was performed to identify risk factors for LEDVT. Receiver operating characteristic (ROC) curve was used to evaluate the overall fit of the final model. There were 56 patients enrolled in the LEDVT group and 81 patients in the NLEDVT group. Age, Aggregate Index of Systemic Inflammation (AISI), Systemic Inflammation Response Index (SIRI), ICU length of stay, and albumin were identified as independent risk factors for LEDVT (all P < 0.05). The area under their ROC curves were 0.604, 0.657, 0.694, 0.668, and 0.405, respectively. Combined model for early clinical prediction of LEDVT in severely traumatized patients by age, SIRI, AISI, and albumin resulted in an area under the ROC curve of 0.805 (95%CI: 0.73-0.88, SE = 0.037). The combination of age, SIRI, AISI, and albumin has a predictive value for LEDVT in severely traumatized patients.